Zarządzanie jakością i zarządzanie wiedzą - współistnienie na przykładzie Gambit-Lubawka Sp. z o.o. - Tabaszewska, Edyta (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The aim of the paper is to describe the relationship between quality management and knowledge management on the basis of research carried out in Gambit-Lubawka Ltd. In the author's opinion we face the coexistence of the both mentioned management conceptions, and not the cooperation, which would be more effective. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (7); 2007; nr 1185, s. 205-214